2017
DOI: 10.18520/cs/v112/i01/95-107
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Irrigation in Rainfed Pigeonpea - Upscaling Productivity under Eastern Gangetic Plains with Suitable Land Configuration, Population Management and Supplementary Fertigation at Critical Stages

Abstract: Water -a critical input for sustained crop production -is becoming limiting both under rainfed and irrigated condition. It calls for an effective on-farm management of water in field crops through microirrigation (drip-fertigation) that could take care of both drainage during rainy months and supplementary life saving irrigation thereafter. Therefore, the present field study involving three planting configurations and five drip-fertigation schedules were taken up in pigeonpea (long duration) during 2010-12 und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 4 publications
2
16
0
Order By: Relevance
“…Application of three supplementary irrigations doubled the seed yields of pigeon pea in alfisols (Chauhan, 1990). These results were further confirmed that depending on water stress, supplementary irrigation was helpful in upscaling grain yield (Praharaj et al, 2017 andRamulu et al, 2020). The results obtained in the present experiment are also in conformity with the findings of Rao et al (1983) and Khanna et al (1980).…”
Section: Water Productivitysupporting
confidence: 93%
“…Application of three supplementary irrigations doubled the seed yields of pigeon pea in alfisols (Chauhan, 1990). These results were further confirmed that depending on water stress, supplementary irrigation was helpful in upscaling grain yield (Praharaj et al, 2017 andRamulu et al, 2020). The results obtained in the present experiment are also in conformity with the findings of Rao et al (1983) and Khanna et al (1980).…”
Section: Water Productivitysupporting
confidence: 93%
“…In this era of life-saving/ supplementary irrigation (mostly adopted in water deficit areas under rainfed/dryland agro-ecosystems), there is a larger need to apply both fertilizers and water through trickle drip especially at critical stages to improve productivity of crop, water and nutrient 8 (Table 1). A single irrigation (20 mm in 5 splits) through drip-fertigation with half of N and K fertilizers at branching of a long duration pigeonpea, produced significantly higher (20%) grain yields and economic return over rainfed crop 1,2,4 . Similarly, an experiment carried out at ICAR-Indian Institute of Pulses Research, Kanpur during 2010-2014 also revealed the compatibility of drip-fertigation with that of intercropping in a wide spaced pulse crop -a long duration pigeonpea.…”
Section: Technological Intervention For Water Managementmentioning
confidence: 99%
“…It enhances conservation of primarily two precious inputs, viz. water and nutrients [4][5][6] . With optimum management of resources, conservation agriculture (CA) -the key input being water -is needed for up-scaling and out-scaling farm productivity.…”
mentioning
confidence: 99%
“…However, blackgram or greengram in coastal peninsular area comprising Odisha, Andhra Pradesh, Tamil Nadu and Karnataka (Table 4). In present days with developed crop management could permit profitable raising of a pulse as a rotational crop after rice (Praharaj et al, 2017).…”
Section: Rice Fallow Pulsesmentioning
confidence: 99%